Cerebrospinal fluid parameters of B cell-related activity in patients with active disease during natalizumab therapy - Harrer, Andrea; Wildemann, Brigitte; Jarius, Sven (Multiple sclerosis journal, 2013)
Recently, the disappearance of oligoclonal bands (OCBs) from the cerebrospinal fluid (CSF) of a few natalizumab-treated patients with multiple sclerosis (MS) has been reported. This is interesting since CSF-restricted OCB are believed to persist in MS. We pooled CSF data from 14 MS centers to obtain an adequate sample size for investigating the suspected changes in central nervous system (CNS)-restricted humoral immune activities in the context of natalizumab therapy. In a retrospective chart analysis, CSF parameters of blood-CSF barrier integrity and intrathecal IgG production from 73 natalizumab-treated MS patients requiring a diagnostic puncture for exclusion of progressive multifocal leukoencephalopathy were compared with CSF data obtained earlier in the course of disease before natalizumab therapy. At the time of repeat lumbar puncture, local IgG production (according to Reibergram) was significantly reduced (p < 0.0001) and OCB had disappeared in 16% of the patients. We therefore conclude that natalizumab therapy interferes with intrathecal antibody production at least in a significant number of patients.
First published October 23, 2012
Gesehen am 26.02.2021